QSIRS Can Improve Accuracy of QSOFA and SIRS in Prediction of Mortality in Surgical Emergencies - Ndong, Abdourahmane; Diallo, Adja Coumba; Tendeng, Jacques Noel; Diallo, Amadou Ibra; Diao, Mohamed Lamine; Sagna, Sylvain Assega; Diop, Saer; Dia, Diago Anta; Diouf, Daouda; Racine, Bayo Ismael; Nyemb, Philippe Manyacka Ma; Konaté, Ibrahima (The Surgery Journal, 2021)
Background The quick sequential organ failure assessment (QSOFA) score and the systemic inflammatory response syndrome (SIRS) criteria were developed to predict the risk of sepsis and death in patients received in emergency. To improve sensitivity in predicting death, the association of the two scores was proposed under the term QSIRS (QSOFA + SIRS). Our aim was to determine the accuracy of QSOFA, SIRS, and QSIRS in prediction of mortality in surgical emergencies, and to compare these scores.Patients and Methods This is a prospective study over a period of 1 year. Patients older than 15 years who presented a digestive surgical emergency (bowel obstruction, peritonitis, appendicitis, strangulated hernia) were included. For each score, the specificity, the sensitivity, the positive predictive value, the negative predictive value, and areas under the receiver operating characteristic (ROC) curve (AUC) were compared.Results One hundred and eighteen patients were included and 11 deaths were recorded (9.3%). There was a statistically significant relationship between each score and death (QSOFA p = 0.01, SIRS p = 0.003, and QSIRS p = 0.004). The realization of the ROC curve found a higher AUC for QSIRS (0.845 [0.767–0.905]) compared with QSOFA (0.783 [0.698–0.854]) and SIRS (0.737 [0.648–0.813]). QSIRS (90.9%) had a higher sensitivity compared with the two other scores alone (SIRS = 81.9% and QSOFA = 36.3%).Conclusion Our study found that QSIRS improves the ability to predict death in digestive surgical emergencies.
Keywords: surgery; emergency; score; QSOFA; SIRS; QSIRS